2021
DOI: 10.1111/psyg.12782
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild behavioural impairment domains: a meta‐analysis

Abstract: Background Mild behavioural impairment (MBI) is a neurobehavioural syndrome characterised by later life emergence of persistent neuropsychiatric symptoms. Our previous meta‐analysis showed that MBI is prevalent among cognitively normal (CN), subjective cognitive impairment (SCI) and mild cognitive impairment (MCI) subjects. This study is to calculate the pooled prevalence of MBI domains among CN, SCI, and MCI subjects. Methods A search of relevant literature published between 1 January 2003 and 6 August 2021 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Indeed, variable MBI diagnostic approaches are a major contributor to heterogeneity in estimates of prevalence of global MBI and domains. 40 , 44 As the MBI-C is a novel instrument, not yet available in cohorts like the Alzheimer’s Disease Neuroimaging Initiative or National Alzheimer’s Coordinating Center, variable symptom durations and NPS measures have been used in many studies. More sensitive and specific prevalence estimates are expected as more MBI-C data become available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, variable MBI diagnostic approaches are a major contributor to heterogeneity in estimates of prevalence of global MBI and domains. 40 , 44 As the MBI-C is a novel instrument, not yet available in cohorts like the Alzheimer’s Disease Neuroimaging Initiative or National Alzheimer’s Coordinating Center, variable symptom durations and NPS measures have been used in many studies. More sensitive and specific prevalence estimates are expected as more MBI-C data become available.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: SCD, subjective cognitive decline; MCI, mild cognitive impairment; NPI-Q, neuropsychiatric inventory questionnaire associated with higher domain scores for apathy, mood/ anxiety, impulse dyscontrol, social inappropriateness, and psychosis, and lower MoCA score. 50%), while fewer had apathy (409/923;44.31%), social inappropriateness (214/923; 23.19%), or psychosis (94/923; 10.18%). Similar trends were observed for each participant group.…”
mentioning
confidence: 99%
“…5 In a meta-analysis of the five MBI domains, the prevalence of affective dysregulation was highest (32.84%), followed by impulse dyscontrol (26.67%), decreased motivation (12.58%), social inappropriateness (6.05%), and abnormal perception or thought content (2.81%). 6 MBI increases the risk of dementia 7,8 and the annual rates of conversion are 14.7% from MBI to dementia and 2.5% from MBI to NC. 9 Since the rates in MCI without neuropsychiatric symptoms are 8.3% and 5.3%, MBI carries a greater risk of dementia than MCI without neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…When considering self or proxy ratings only, the proportion of people in our sample with MBI‐psychosis (self: 3%; proxy: 6%) is broadly in line with the 2.8% (95% CI: 1.7–4.7%) prevalence in other cognitively normal studies reported in a recent meta‐analysis. 13 The combined proportion is 9% (i.e., either self‐ or proxy‐rated MBI‐psychosis) because there is very little overlap between self and proxy ratings. This estimate is higher than most (but not all 12 ) other studies in cognitively normal people, and further exploration of the significance of the lack of overlap will be an important avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In cognitively normal older individuals, psychosis prevalence when assessed in the MBI framework is ≈3% but has been reported as high as 10%–12% (henceforth MBI‐psychosis). 11 , 12 , 13 In people with normal cognition, most studies are focused on clinically defined groups of patients with psychotic disorders (e.g., delusional disorder, late‐onset schizophrenia, or very‐late‐onset schizophrenia‐like psychosis). Overall, these tend to show an increased risk of dementia; however, studies on individuals whose symptoms are not attributable to another clinical disorder are scarce.…”
Section: Introductionmentioning
confidence: 99%